Efficient Implementation with Interdependent Valuations and Maxmin Agents - Yangwei Song (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
We consider a single object allocation problem with multidimensional signals and interdependent valuations. When agents signals are statistically independent, Jehiel and Moldovanu show that efficient and Bayesian incentive compatible mechanisms generally do not exist. In this paper, we extend the standard model to accommodate maxmin agents and obtain necessary as well as sufficient conditions under which efficient allocations can be implemented. In particular, we derive a condition that quantifies the amount of ambiguity necessary for efficient implementation. We further show that under some natural assumptions on the preferences, this necessary amount of ambiguity becomes sufficient. Finally, we provide a definition of informational size such that given any nontrivial amount of ambiguity, efficient allocations can be implemented if agents are sufficiently informationally small.
Keywords: D61; D82; 330; efficient implementation; ambiguity aversion; multidimensional signal; interdependent valuation